1987
DOI: 10.1101/gad.1.4.358
|View full text |Cite
|
Sign up to set email alerts
|

Retroviral transfer and expression of the interleukin-3 gene in hemopoietic cells.

Abstract: A recombinant retrovirus containing the interleukin-3 (IL3) coding sequence and the neomycin-resistance gene (Neo') has been generated. Infection of fetal liver cells with the IL3 retrovirus, but not with the N2 parental virus, resulted in the formation of factor-independent, Neo R colonies containing various types of differentiated hemopoietic cells. Established cell lines could be generated from these mixed hemopoietic colonies. These cell lines contained the unrearranged viral genome, produced viral IL3, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
1

Year Published

1988
1988
2007
2007

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 32 publications
1
38
0
1
Order By: Relevance
“…Introduction of the mouse gene for GM-CSF into a factor-dependent hematopoietic cell line (FDC-P1) resulted in autonomous growth and tumorgenicity (20). Analogous results have been obtained with the murine IL-3 gene (14,15,38). In some cases, autonomous growth appeared to depend on secretion of the growth factor (14,15,18), whereas cell proliferation of other growth factor-producing lines was insensitive to cell density and neutralizing antibody (6,20).…”
supporting
confidence: 57%
“…Introduction of the mouse gene for GM-CSF into a factor-dependent hematopoietic cell line (FDC-P1) resulted in autonomous growth and tumorgenicity (20). Analogous results have been obtained with the murine IL-3 gene (14,15,38). In some cases, autonomous growth appeared to depend on secretion of the growth factor (14,15,18), whereas cell proliferation of other growth factor-producing lines was insensitive to cell density and neutralizing antibody (6,20).…”
supporting
confidence: 57%
“…Although initial reports suggested that aberrant factor expression leads directly to tumorigenic growth [6,8,9], the studies presented here and elsewhere [5,7,17] have clearly demonstrated that secondary events are necessary for true autonomous growth and increased tumorigenic potential. These secondary events may be dependent on the autogenous factor production or may have obtained selective advantage in cells producing their own factor.…”
Section: G Outlookmentioning
confidence: 94%
“…Tumorigenesis of hemopoietic cells and acquisition of factor independence as a consequence of aberrant growth factor release are closely correlated [5][6][7][8][9]. In previous work we were able to dissect two stages leading to growth factor autonomy of cells: the first step requires the secretion of the constitutively expressed CSF gene product and extracellular interaction with its cognate receptor.…”
Section: F Summary and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Divers arguments en faveur de cette théorie ont été apportés par la génétique moléculaire (Duesberg, 1987 (Land et al, 1983). Un ré-sultat identique est obtenu lorsque l'oncogène ras est associé à l'oncogène N-myc (Yancopoulos et al, 1985), ou au protooncogène dérégulé c-jun (Schütte et al, 1989) Green, 1989;Weinberg, 1985 (Schwartz et al, 1986;Vaux et al, 1988 (Thompson et al, 1989 (Rüther et al, 1987(Rüther et al, , 1988 (Sinn et al, 1987 (Frykberg et al, 1983;Kahn et al, 1984;Johnson et al, 1989;Morishita et al, 1988;Carmier et Samarut, 1986;Lang et al, 1987;Wong et al, 1987;Neufeld et al, 1988 (Rosenthal et al, 1986;Stern et al, 1987;Jaye et al, 1988;Sasada et al, 1988;Rogelj et al, 1988 …”
Section: Introductionunclassified